The adoption of improved varieties (SFL-09 and SFL-11) has contributed to lower costs for almost 6 out of 10 rice farmers in Ecuador between 2014 and 2019. - CGIAR Research Program on Rice (2021)
The Alliance Bioversity-CIAT and The Latin American Fund for Irrigated Rice-FLAR have contributed to improving the quality of rice germplasm to strengthen rice production across Latin America. In Ecuador, the main variety adopted comes from the FLAR breeding program. Its adoption has been associated with lower production costs, greater probability of adopting other technologies, and better use of inputs.